An object-oriented introduction to data structures using Eiffel - Wiener, Richard S. (Prentice Hall, 1997)
Introduces object-oriented data structures using Eiffel, a language that is ideal for the beginning programmer.Introduces abstract data types, encapsulation, classes, external and internal views of classes, inheritance and polymorphism. Presents an overview of the Eiffel Language and its advantages. Introduces Eiffel's ARRAY and STRING classes and several standard sorting algorithms. Introduces stack and queue abstractions, in both static and dynamic implementations. Presents the basics of recursion and lists. Also introduces binary trees and search trees, presenting important algorithms for balancing search trees.Anyone who wishes to learn object-oriented techniques without encountering the complexity of C++.